2021
DOI: 10.1093/rheumatology/keab116
|View full text |Cite
|
Sign up to set email alerts
|

JAK inhibitors are effective in a subset of patients with juvenile dermatomyositis: a monocentric retrospective study

Abstract: Objective To evaluate the efficacy and safety of JAK inhibitors (JAKi) in juvenile dermatomyositis (JDM). Methods We conducted a single-center retrospective study of patients with JDM treated by JAKi with a follow-up of at least 6 months. Proportion of clinically inactive disease (CID) within six months of JAKi initiation was evaluated using PRINTO criteria and skin Disease Activity Score. Serum IFN-α concentration was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 23 publications
3
55
0
2
Order By: Relevance
“…Previous study showed JAK inhibitor can restore muscle strength, signi cance improvement was observed after short usage [14,27,28]. In our study, one patient with severe muscle weakness was improved markedly (CMAS 15 to 30) upon baricitinib at 4 weeks of treatment.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Previous study showed JAK inhibitor can restore muscle strength, signi cance improvement was observed after short usage [14,27,28]. In our study, one patient with severe muscle weakness was improved markedly (CMAS 15 to 30) upon baricitinib at 4 weeks of treatment.…”
Section: Discussionsupporting
confidence: 55%
“…Voyer and his colleague reported a new-onset case with severe skin ulcerations got CR after 1.7 months of baricitinib initiation [14].Calci cation is a therapeutic challenge in JDM. Data was limited in the treatment of JAKi in calci cation, one paper displayed that only partially regressed was observed in a case who had JDM complicated with calci cation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for other interferonopathies, the precise role of IFN-I in the pathology for jDM, and whether it is driving or secondary to the disease progression has been amply discussed. Using Digital ELISA, it was shown that circulating INF α levels in jDM patients correlate with disease activity [23 , 36] and response to treatment [37] . Furthermore, PBMCs isolated from jDM patients display a spontaneous production of IFN α in culture [38] .…”
Section: Article In Pressmentioning
confidence: 99%
“…Overall tolerance was good except for a high rate of herpes zoster infection. No severe adverse events (SA) or death related to the use of JAKIs were reported [37] . Thus, JKAIs seem a promising new targeting treatment of jDM.…”
Section: Diagnostic Algorithms Consensus Papers On Juvenile Myositismentioning
confidence: 99%